INTEGRATING ENGLISH LANGUAGE AND VALUES EDUCATION TO DEVELOP MEDIA COMPETENCE IN FUTURE PRIMARY SCHOOL TEACHERS (International journal of artificial intelligence, 2025)
This article examines the integration of English language teaching with values education as a means of developing media competence in future primary school teachers. It highlights the role of media-based activities—such as role plays, visual materials, and storytelling—in fostering communicative, ethical, social, and media literacy skills. The study concludes that combining language learning with values-oriented media content enhances students’ personal qualities and prepares teachers to effectively integrate language, ethics, and media tools in education.